Lectora Inspire Learning Media Based on Character Education in PPKn Learning for Grade III Elementary Students - Audia, Fyra Aldira; Zakiah, Linda; Utami, Nidya Chandra Muji (Universitas Pendidikan Ganesha, 2021)
In revolution 4.0, technology has an important role in the education sector one of them to making digital media learning there are values on character education by the purpose of learning on the curriculum 2013.Â This study aims to designed Lectora to inspire learning media-based character education on PPKn for students in class III elementary school and measuring the media. Research methodology uses the research and development model of Hannafin and Peck. To technique data collection to students, teachers, and validation by 3. expert. Analysis technique quantitative data based on the calculation of answers in Likert scale. The result of validation data from material experts with a score of 87.5%, validation result from media experts with a score of 85%, validation result from language experts with a score of 81%, and grade III teachers with a score of 98%. The learning media Lectora inspire based character education who then tried out on 15 students grade III Elementary School with a score of 98%. By looking at the result, it can be said Lectora inspires learning media-based character education on PPKn for students in class III elementary school appropriate to be used as medium learning.